THE USE OF FSLC TECHNIQUE TO PROMOTE ELEVENTH GRADE STUDENTS OF SMAN 2 PONTIANAK TO SPEAK ENGLISH - Setyarini, Nurul Sabrina; Aprilias, Rahayu; Arifin, Zainal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Email : nurul.sabrina2013@gmail.com Abstract: This research is aimed on how the use of FSLC technique which comes from cooperative learning strategy, could promote students to speak English. Particularly on how the activities in each stage of FSLC technique (formulateÂ share, listen, and create stage) could promote students' pronunciation, vocabulary, and ideas in speaking English. This research was a Classroom Action Research which was conducted in three cycles. The research subjects were the students of class XI MIA 4 at SMA Negeri 2 Pontianak. The data were collected by observation, recording, and questionnaire. The result indicated that Formulate Stage promoted students to use relevant vocabulary and sufficient ideas in speaking English. Share-Listen Stage promoted students to speak with better pronunciation and relevant vocabulary by actively sharing, discussing, and correcting pronunciation. Create Stage promoted students to speak with sufficient ideas as well as they collaborated the ideas. In conclusion, FSLC technique successfully promoted students to actively speaking English in teaching learning process. Keywords: FSLC Technique, Speaking English, Pronunciation, Vocabulary, Ideas Abstrak : Penelitian ini bertujuan untuk mengetahui bagaimana tehnik FSLC dari strategy pembelajaran kooperatif, dapat mendorong siswa berbicara Bahasa Inggris. Terutama bagaimana aktivitas di setiap tahapan tehnik FSLC (Tahap Formulate, Share, Listen, dan Create) dapat mendorong siswa berbicara Bahasa Inggris dengan pengucapan, kosakata, dan ide-ide yang lebih baik. Penelitian ini menggunakan metode Penelitian Tindakan Kelas yang dilakukan selama tiga siklus. Subjek penelitian ini adalah siswa kelas XI MIA 4 di SMA Negeri 2 Pontianak. Data-data yang diperoleh melalui observasi, rekaman, dan kuisioner ini, menunjukkan bahwa Tahap Formulate telah mendorong siswa menggunakan kosakata relevan dan ide yang cukup dalam berbicara. Tahap Share-Listen dapat mendorong siswa untuk berbicara dengan pengucapan yang lebih benar dan kosakata yang relevan melalui berbagi ide, berdiskusi, dan mengkoreksi pengucapan satu sama lain. Tahap Create juga mendorong siswa untuk berbicara dengan ide yang cukup melalui kolaborasi ide yang mereka lakukan. Kesimpulannya, tehnik FSLC dapat mendorong siswa untuk bisa lebih aktif berbicara Bahasa Inggris dalam proses pembelajaran. Kata Kunci: Tehnik FSLC, Berbicara Bahasa Inggris, Pengucapan, Kosakata, Ide-ide.